Standard static compression stress strain test - Muhamad Faizal Bin Rosli (2016)
This Final Year Project (FYP) report showcases the work of the Project Title Standard Static Compression Stress Strain Test. The Project Number is B240. The aim of this report is to provide readers with the whole synopsis of this FYP. This project is of accordance and referenced to part of a senior’s FYP report done in year 2008/2009. This report is divided into several sections that describe the areas of progress for the FYP from the start to finish. There are 6 sections in total in this report beginning with the introduction the project. The introduction covers the background, rationale of project, objectives and scope of this FYP. The objectives of this FYP are to conduct standard static compression test conformable to the American Society for Testing Materials (ASTM) standards and compare the results obtained from the test to other past studies and researches. Furthermore, there would also be recommendations given in order to improve test procedures. The second section in this report covers the detailed explanations and procedures in conducting compression testing of metallic materials from ASTM International standards. It also encompasses the explanations of important terms that are relevant in compression tests. There will be a short summary of the material, Aluminium alloy 6061-T6 (Al6061-T6) that is used in this project that includes the material properties and chemical composition. The third section in this report consists of the fabrication of the Al6061-T6 specimen followed by polishing. The preparation of specimen process is explained in this portion from deciding the suitable dimensions to designing of specimen to fabricating the specimens itself in the workshop. The procedures for fabrication of specimens are included as well. Polishing method is briefly explained in this section. The fourth section describes the experimental setup and procedure for the compression testing. The machine used for the test is Universal Testing Machine, Instron 5500. Procedures are explained in detail in setting up both the Instron Bluehill program and the test machine itself. The results and discussions of the compression tests are covered in the fifth section. The results obtained are analysed and carefully interpreted for accuracy. Comparison of the results with past researches will be discussed and assessed in this section. The last section encompasses the conclusion and recommendations for compression testing of metallic materials. The conclusions on standard compression test are being discussed regarding the extent of which conditions of ASTM standards are met. The ideas on how the compression testing procedures could be improved are also mentioned in this part.